The Range of Rejoicing in Luke-Acts: Exploring the Precision and Power of Luke's Positive Emotion Terminology - Bruehler, Bart B. (Journal for the study of the New Testament, 2026)
The author of Luke-Acts demonstrates granularity and skill in his precise use of positive emotion terminology, here labelled as "rejoicing". The theory of culturally constructed emotions and the use of semantic mapping provide helpful tools for analysing the range of rejoicing terminology in Luke-Acts. This study compares Luke's positive emotion terminology with Josephus's Antiquities and the Septuagint. This demonstrates that Luke does have a significant percentage of rejoicing terminology and that he uses a range of word families with consistent precision. Luke's emotional skill supports his rhetorical skill, enabling him to move and persuade his audience. Finally, the handful of instances where Luke combines positive emotion terminology is shown to reinforce their specific connotations.